2023
DOI: 10.1038/s41598-023-49173-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of choledochotomy primary closure in laparoscopic common bile duct exploration without biliary drainage: a retrospective study

Wei Lai,
Nan Xu

Abstract: Common bile duct (CBD) exploration and T-tube drainage are the main surgical methods for the removal of bile duct stones (BDSs), which can now be completed by laparoscopy. However, the feasibility and safety of primary closure of the CBD (PCCBD) in laparoscopic CBD exploration (LCBDE) without biliary drainage are still uncertain. From January 1, 2021, to June 30, 2022, patients who were diagnosed with BDSs and underwent LCBDE and primary closure of the CBD without biliary drainage in our hospital were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, in some cases, long-term bile reflux caused by an incision in the sphincter of the ampulla of Vater may lead to the recurrence of bile duct stones and the development of biliary tract tumors [ 13 , 14 ]. Laparoscopic common bile duct exploration (LCBDE), which involves laparoscopic choledochotomy for stone removal combined with choledochoscopy, has emerged as an advantageous approach [ 15 ]. Studies have indicated that LCBDE is often a preferred option in many cases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in some cases, long-term bile reflux caused by an incision in the sphincter of the ampulla of Vater may lead to the recurrence of bile duct stones and the development of biliary tract tumors [ 13 , 14 ]. Laparoscopic common bile duct exploration (LCBDE), which involves laparoscopic choledochotomy for stone removal combined with choledochoscopy, has emerged as an advantageous approach [ 15 ]. Studies have indicated that LCBDE is often a preferred option in many cases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of postoperative complications revealed that patients in the primary closure group had the highest incidence of bile leakage. Further investigation revealed that this occurrence was primarily due to an excessive number of stones within the bile duct [ 15 ]. The occurrence of such complications is attributed to repeated manipulation of the sphincter of the ampulla of Vater during stone extraction, resulting in spasms, edema, and even bleeding [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation